A survey of cellular IP in the next generation of network protocol - Mohd Shabli, Ahmad Hanis; Omar, Hasbullah; Hassan, Suhaidi (Universiti Utara Malaysia, 2008)
The main objective of mobility management in wireless data communication is to allows networks to search and locate (location management) mobile users while maintaining it’s connections (handoff management) whenever users move into a new network. Management of location and handoff divided into macromobility (for managing inter-domain network) and micromobility (for managing intra-domain network).For macromobility management, IETF has adopted Mobile IP and had perform very well for managing inter-domain mobility.However Mobile IP suffer from handover performance in intradomain network which is inefficient for mobile user with frequent handoff. For this defect,cellular IP protocol has been considered for managing intra-domain network for it’s fast handoff and interoperability with Mobile IP. This paper we present a review of different micro-mobility management protocols available to date. We also discuss various issues and challenges regarding mobility management for the next generation network protocol.